Makna Simbolik Rumah Adat Sa’o Bei Zi’a dalam Implementasi dan Pendekatan Etnopedagogi Berbasis Kearifan Lokal Masyarakyat Ngada: Penelitian - Virgilius Bate Lina; Agus Tryani; Maria Yanty Soi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Abstract: This study aims to examine the symbolic meaning of the Sa’o Bei Zi’a traditional house as a representation of cultural values within the Ngada community and its relevance in implementing an ethnopedagogical approach based on local wisdom. The Sa’o Bei Zi’a house functions not only as a residence but also as a spiritual, social, and informal educational center that reflects noble values such as mutual cooperation, social hierarchy, and harmonious relationships with nature. A qualitative approach using literature review and in-depth interviews was employed to explore its symbolic meanings and educational potential. The findings indicate that the structure and ornaments of the traditional house contain moral and pedagogical messages that can be integrated into the learning process, particularly in shaping students' character rooted in local culture. The ethnopedagogical approach based on Sa’o Bei Zi’a offers an alternative model of contextual education that strengthens cultural identity and responds to the challenges of globalization without abandoning traditional roots.